IDENTIFIKASI SENYAWA ANTIOKSIDAN DARI EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius) DENGAN METODE 2,2-DIPHENYL-1-PICRYL-HYDRAZYL ( DPPH ) - Hashary, A Rufaidah; Damayanti, Utami Putri; Rusdiaman, Rusdiaman; Nurzak, An Nisaa (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Pandan wangi (Pandanus amaryllifolius) is one type of monocotyledonous in the Pandanaceae family that has leaves with a characteristic fragrant aroma. There is a chemical content in the leaves of pandan wangi (Pandanus amaryllifolius) namely alkaloids, flavonoids, saponins, tannins, and polyphenols that can be used as natural antioxidants. This study aims to identify the presence of antioxidant compounds in ethanol extract of pandan wangi leaves (Pandanus amaryllifolius). The research method is an experimental method. The extraction process by maceration and antioxidant testing of pandan wangi leaves (Pandanus amaryllifolius) ethanol extract used the DPPH method where Vitamin C being a positive control, and IC50 value as a parameter. The results stated that ethanol extract of Pandan wangi leaves (Pandanus amaryllifolius) has antioxidant activities that are classified as effective with an IC50 value of 27.65 ppm, while Vitamin C as positive control is classified as an effective antioxidant with an IC50 value of 2.58 ppm. Based on the results of the research that has been done, it can be concluded that the ethanol extract of Pandan Wangi leaves has a good antioxidant content in counteracting free radicals.